Balanço de macronutrientes no Açude Gavião/CE: uma nova abordagem - Vidal, Ticiana Fontoura (2011)
The study area, the reservoir Gavião, is positioned in the northeastern state of Ceara, is inserted in the municipality of Pacatuba and located upstream of the Water Treatment Plant - ETA, responsible for supplying drinking water in the Metropolitan Region Fortaleza.Os reservoirs in the state of Ceará, specifically those located in metropolitan areas of the basins, such as dam Hawk, are targets of impacts resulting from various human activities developed along its watershed. Water eutrofizadasproporcionam greater difficulty and high treatment costs, mainly due to the presence of excessive algae. This increasing growth of algae in the waters are the result of continuous delançamentos nutrients, especially nitrogen and phosphorus, which modify the characteristics of water bodies as well as its quality. An important tool for the definition of strategies recovery, storage and management of a watershed is to determine the nutrient load, which has the purpose of evaluating the eutrophication process over a system as well as determining the mass balance through estimates of inputs, outputs and retention of nutrients in the water body. To this end, samples were collected monthly from December 2010 to May 2011, at five different points of the dam, in order to study the mass balance of macronutrients, check the quality of stored water, draw vertical profiles of physical and chemical parameters and determining the limiting nutrient in the system. During the study period, the dam has accumulated over 28.06 tons of 121.42 tons of phosphorus and nitrogen. The concentrations of the investigated parameters estãocada higher and higher and the limitation has always been of the nitrogen fraction (N / P <10), the reservoir Gavião may be classified as eutrophic.